2004
DOI: 10.1037/0033-295x.111.4.835
|View full text |Cite
|
Sign up to set email alerts
|

Linear theory, dimensional theory, and the face-inversion effect.

Abstract: We contrast 2 theories within whose context problems are conceptualized and data interpreted. By traditional linear theory, a dependent variable is the sum of main-effect and interaction terms. By dimensional theory, independent variables yield values on internal dimensions that in turn determine performance. We frame our arguments within an investigation of the face-inversion effect-the greater processing disadvantage of inverting faces compared with non-faces. We report data from 3 simulations and 3 experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 58 publications
(85 reference statements)
4
111
0
Order By: Relevance
“…It is consistent with a growing body of work, coming mainly from computational and formal quarters (Ellison & Massaro, 1997;Gold et al, 2012;Loftus et al, 2004;Macho & Leder, 1998;Tversky & Krantz, 1969;Bradshaw & Wallace, 1971;Wenger & Townsend, 2006;Donnelly et al, 2012;Wenger & Ingvalson, 2002; that defy the notion of holistic processing. Particularly relevant here is a recent study by Donnelly, Cornes, and Menneer 2012, who have applied the capacity coefficient to the Thatcher illusion (Thompson, 1980).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is consistent with a growing body of work, coming mainly from computational and formal quarters (Ellison & Massaro, 1997;Gold et al, 2012;Loftus et al, 2004;Macho & Leder, 1998;Tversky & Krantz, 1969;Bradshaw & Wallace, 1971;Wenger & Townsend, 2006;Donnelly et al, 2012;Wenger & Ingvalson, 2002; that defy the notion of holistic processing. Particularly relevant here is a recent study by Donnelly, Cornes, and Menneer 2012, who have applied the capacity coefficient to the Thatcher illusion (Thompson, 1980).…”
Section: Discussionmentioning
confidence: 92%
“…Operational studies often support the notion of facial holism whereas quantitative computational models are much less supportive. Studies from the latter tradition have shown that facial features can stand the strong tests of: statistical independence (Ellison & Massaro, 1997;Gold et al, 2012;Loftus et al, 2004;Macho & Leder, 1998), geometrical independence (Sergent, 1984;Tversky & Krantz, 1969), independence in processing rate (Bradshaw & Wallace, 1971;Wenger & Townsend, 2006;Donnelly et al, 2012), and perceptual independence (Wenger & Ingvalson, 2002, but see, Mestry et al, 2012).…”
Section: Facial Holism: Operational Versus Theoretical Accountsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the key conceptual claim of COVIS is that there are two mechanisms of learning, it could be argued that these analyses have failed to identify multiple systems only because the difference in learning between training types just happened to be the same for rule-based and information-integration learning by the end of training. To examine the validity of this claim, we used state-trace analysis (Bamber, 1979;Loftus, Oberg, & Dillon, 2004), which has previously been used with great success on this type of category learning data Dunn et al, 2012).…”
mentioning
confidence: 99%
“…Although these approaches are promising and each have merit, we do not implement them here due to our combination of within-and between-subjects measures, and the high dimensionality of the stimuli used in Experiment 2. Rather, we use a more conventional approach based on confidence intervals (e.g., Busey, Tunnicliff, Loftus, & Loftus, 2000;Loftus, Oberg, & Dillon, 2004). In particular, we construct least-significant difference (Saville, 2003) ellipses around data points on a state-trace graph, with these ellipses based on Morey's (2008) modification of Loftus and Masson's (1994) within-subject standard errors for within-subjects comparisons.…”
Section: Analytic Approachmentioning
confidence: 99%